Accurate Determination of Elemental Contents in Carbonate Minerals with Laser Ablation Inductively Coupled Plasma-Mass Spectrometry - Tao LUO; Liyuan QING; Jinyu LIU; Wen ZHANG; Tao HE; Zhaochu HU (Yankuang ceshi)
BACKGROUNDTrace element information in carbonates provides key constraints for investigating ancient environments, paleoclimate evolution, shell-mantle interactions, diagenesis and mineralization processes. The accurate determination of trace element content in carbonate minerals have always been a primary focus. Laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) can provide detailed information on trace element content in carbonate minerals. However, the elemental concentrations in carbonate minerals are usually extremely low (from hundreds of pg/g to tens of ng/g). A large spot size (from 44 to 100μm) is often used for trace element measurements in carbonate minerals. Therefore, the detection capability of low-content elements in carbonate minerals and the spatial resolution of LA determination still need to be improved.OBJECTIVESTo develop a new analytical method for determination of low-content trace elements in carbonate minerals with LA-ICP-MS.METHODSA new local aerosol extraction ablation cell was proposed in this study. Laser ablation was performed using high-repetition rates with the new designed ablation cell. The elemental contents in carbonate reference materials MACS-3, CGSP-A, CGSP-B, CGSP-C, and CGSP-D were determined with both ns and fs LA-Q-ICP-MS with a spot size of 32μm. Here, NIST 610 glass was used as an external calibration material and Ca was used as an internal standard.RESULTSThe obtained peak height of a single laser shot was enhanced by a factor of 13 with the local aerosol extraction ablation cell because of the rapid washout time. The signal intensities were increased by 1.5 times under high-repetition rate laser ablation mode. Therefore, the detection limits of trace elements in carbonate minerals obtained from nanosecond laser ablation at high repetition rates (20Hz) were reduced by 5-8 times compared to conventional analysis (6Hz). The detection limits of trace elements were reduced by 5-10 times with the frequency of femtosecond laser ablation increased from 10Hz to 100Hz. The elemental contents in carbonate reference materials were measured with both ns and fs LA-Q-ICP-MS with a spot size of 32μm. The obtained results of lithophile elements (e.g., Sc, Sr, Y, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Th) in carbonate CGSP series and carbonate MACS-3 showed good agreement with their reference values. However, the measured results of siderophile and chalcophile elements (e.g., Ni, Cu, Zn, As, Cd, Sn, Sb, and Pb) showed systematic bias (>20%), which may be related to the “downhole” fractionation effect caused by the high-repetition rate laser ablation used in this study.CONCLUSIONSThe new designed local aerosol extraction ablation cell combined with high-repetition rate laser ablation mode significantly improved the spital resolution and determination ability of low-content elements in carbonate minerals. The obtained results of lithophile elements in carbonate CGSP series and carbonate MACS-3 showed good agreement with their reference values using ns- and fs-LA-Q-ICP-MS with a spot size of 32µm. It is worth noting that the spatial resolution and the detection capability of ultra-low-content elements in carbonate minerals could be further improved with the proposed LA method combined with high-sensitivity magnetic sector mass spectrometry.